Desenvolvimento de compósitos bioativos a base de PBAT e PLA com adição de hidroxiapatita e tanino para aplicação em engenharia de tecidos - Bezerra, Ewerton de Oliveira Teotônio (Universidade Federal de São Carlos, 2024)
The increase in the population's life expectancy has increased the demand for orthopedic procedures aimed at bone repairing, driving the development of new materials to assist in tissue regeneration. In this context, this project aimed to obtain biocomposites for manufacturing bioactive scaffolds via 3D printing, aiming at bone regeneration. The biocomposites were based on Ecovio® (Poly(lactic acid) - PLA/ Poly(adipate butylene co-terephthalate) - (PBAT)), hydroxyapatite (HA) and an amino-functionalized derivative of tannin (TN). In the first stage, TN purification was performed to remove impurities from its synthesis process. The next step involved the processing of the Ecovio biocomposites in which both HA and purified tannin (pTN) were incorporated in a proportion of 10wt% each, using an internal mixer. Thermal, rheological, morphological, and mechanical characteristics, as well as printability, bioactivity, and antimicrobial activity, were investigated. In the last stage, Ecovio® scaffolds were 3D printed, followed by surface modifications with alkaline treatment and subsequent addition of pTN and HA in order to optimize their biological properties. The morphological, mechanical, wettability, surface roughness, bioactivity, and cell biocompatibility were evaluated. The results showed that the purification of TN was successful and suggest that the addition of pTN and HA did not degrade the polymer matrix, conferring bioactivity and bactericidal efficacy in the compositions with pTN. The superficial modifications were successfully performed regarding the scaffolds, optimizing their biological properties, such as bioactivity and biocompatibility, favoring cell proliferation. The biological and mechanical properties of the scaffolds showed that the materials developed are compatible with the requirements for application as bone grafts.
Development of bioactive composites based on PBAT and PLA with the addition of hydroxyapatite and tannin for application in tissue engineering
Keywords: Ecovio; Taninos; Hidroxiapatita; Regeneração óssea; Scaffolds; Manufatura aditiva; Tannins; Hydroxyapatite; Bone regeneration; Additive manufacturing; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS